2018
DOI: 10.1515/hf-2018-0026
|View full text |Cite
|
Sign up to set email alerts
|

The gene expression and enzymatic activity of pinoresinol-lariciresinol reductase during wood formation in Taiwania cryptomerioides Hayata

Abstract: Taiwania (Taiwania cryptomerioidesHayata) is an indigenous conifer species of Taiwan. Various secondary metabolites of Taiwania with diverse bioactivities have been identified, and lignans are especially abundant in the heartwood (hW). In the present study, the wood of this species was separated to cambium (Cam), sapwood (sW), transition zone (TZ) and hW and their transcriptomes were sequenced. Three pinoresinol-lariciresinol reductases (PLRs; designatedTcPLR1,TcPLR2.2andTcPLR3), which are responsible for lign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…Chiang et al . found that the lignan synthesis‐related TcPLR gene of Taiwania cryptomerioides had a higher expression level in the phloem and cambium 43 . In our study, velvet ash could resist EAB larva infestation by up‐regulating FvPLR1 gene expression to increase lignan synthesis.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Chiang et al . found that the lignan synthesis‐related TcPLR gene of Taiwania cryptomerioides had a higher expression level in the phloem and cambium 43 . In our study, velvet ash could resist EAB larva infestation by up‐regulating FvPLR1 gene expression to increase lignan synthesis.…”
Section: Discussionsupporting
confidence: 47%
“…The regulation of PLR gene expression, as well as potential reductase specificities for one reduction step, are important factors in fine‐tuning lignan synthesis 42,43 . A lariciresinol isolated from Arabidopsis thaliana has two annotated genes as PLR (PLR1 and PLR2), clearly demonstrating that lariciresinol is involved in enantiomeric control in lignan biosynthesis 44 .…”
Section: Discussionmentioning
confidence: 99%
“…In the metabolic pathway of phenylalanine, a series of intermediates such as coumaric acid, caffeic acid, ferulic acid, and cinnamic acid are produced, which are then converted to lignans and other substances catalyzed by various enzymes. PAL, C4H, 4CL, and PLR are the most studied enzymes that play an important role in lignans biosynthesis ( Chiang et al., 2019 ; Vanholme et al., 2019 ), and these related to lignans biosynthesis pathway genes were identified in our RNA-seq data set. PAL catalyzes the first step of phenylalanine reaction and converts phenylalanine to cinnamic acid by deamination.…”
Section: Resultsmentioning
confidence: 99%
“…The types of induced programmed cell death (PCD) in Taiwania were analyzed based on Olvera−Carrillo and his coworkers' method [28], who introduced PCD−related genes, including 25 developmentally induced PCD−related genes, 27 biological factor−induced PCD−related genes, 27 osmotic pressure−induced PCD−related genes, and 30 genotoxicity−induced PCD−related genes, a total of 109 induced PCD−related genes by 82 experiments (Table S1). These gene sequences were then searched and compared to the transcriptome database of Taiwania established by Professor Chu's group [22,28,40]. We got each gene expression (FPKM) in developing xylem (DX), sapwood (SW), and transition zone (TZ) from the database.…”
Section: Analysis For Types Of Induced Programmed Cell Deathmentioning
confidence: 99%
“…The phytochemistry of Taiwania have been studied since the 1930s. More than hundreds of compounds with bioactivities have been identified from different parts of Taiwania [1,2,21,22]. Taiwania is the appropriate material for studying heartwood formation, due to it can easily distinguish the heart wood, sapwood wood, and transition zone according to the color.…”
Section: Introductionmentioning
confidence: 99%